Case report of renal manifestations in X-linked agammaglobulinemia - Wan, Shuisen; Cao, Meiling; Zou, Jiahui; Bai, Yaojia; Shi, Mingyue; Jiang, Hongkun (Frontiers in Immunology, 2024)
Introduction: X-linked agammaglobulinemia (XLA) is a humoral immunodeficiency disorder characterized by recurrent infections, severe hypogammaglobulinemia, and a deficiency of circulating B cells. While the hallmark clinical manifestations of XLA typically include the respiratory, dermatological, and gastrointestinal systems, renal involvement is infrequent. In this article, we report two cases of XLA with concurrent renal disease, supplemented with a review of documented cases. Case description: The two cases described involve twin brothers, both presenting with respiratory tract infections and renal manifestations. Subsequent genetic testing confirmed the diagnosis of XLA. The younger brother exhibited improvement following intravenous immunoglobulin (IVIG) therapy and anti-infection treatment. Due to financial constraints, the older brother received only anti-infection and symptomatic treatments. Seven months after discharge, the older brother developed nephritis. However, he showed improvement following IVIG treatment. Conclusion: Immune profiling and genetic testing should be considered in male children with recurrent infections to facilitate the effective diagnosis of XLA. Regular monitoring is also imperative to detect and treat immune-mediated renal diseases in patients with XLA.